FORMATION OF PROFESSIONAL COMPETENCE IN PHILOLOGY STUDENTS (American Journal of Research in Humanities and Social Sciences, 2023)
The article emphasizes the need to develop professional communicative competence among philology students, which helps future specialists to successfully solve communicative tasks of a professional nature. The expediency of systematic work based on a set of exercises is substantiated.